Economic Aspects of Adulteration and Imitation - Alsberg, Carl L. (Quarterly Journal of Economics, 1931)
Introduction, 1. — I. Definition of terms, 2. — II. Reactions to a falsified good: (1) the genuine is displaced, 8; (2) both remain in use, 11; (3) the falsified disappears, 13; (4) the demand for both falls, 13; (5) the demand for both increases, 16. — Importance of knowledge, 17. — III. Effect of conditions of production, 20; of elasticity of supply, 21. — IV. Effect of legal enactments: labelling, 23; grading, 25. — V. Effect upon the national economy and the final user, 26. — Waste, 27. — Introduction of novelties, 30. — Expense for protection, 31.